2015
DOI: 10.7567/jjap.54.08kd09
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sputter-induced ion bombardment at the heterointerfaces of a-Si:H/c-Si solar cells with double-layered In2O3:Sn structures

Abstract: The effect of ion bombardment on photovoltaic characteristics, induced during the sputtering deposition of In 2 O 3 :Sn (ITO) layers, has been investigated using hydrogenated amorphous silicon/crystalline silicon (a-Si:H/c-Si) heterojunction solar cells with double-layered ITO structures. The experimental results indicate that the significant decrease in the fill factor (FF) induced at a sputtering rf power higher than 30 W is attributed to the increase in series resistance (R s ), which is caused by property … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These three types of TCOs are commonly used in SHJ solar cells. 6,9,[17][18][19] In this work, the dopant concentrations were 1.0 wt % WO 3 , 5.0 wt % SnO 2 , and 3.0 wt % TiO 2 for IWO, ITO, and ITiO, respectively.…”
Section: Experimental Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…These three types of TCOs are commonly used in SHJ solar cells. 6,9,[17][18][19] In this work, the dopant concentrations were 1.0 wt % WO 3 , 5.0 wt % SnO 2 , and 3.0 wt % TiO 2 for IWO, ITO, and ITiO, respectively.…”
Section: Experimental Methodsmentioning
confidence: 96%
“…Therefore, a TCO film with excellent optical and electrical properties is vital for SHJ solar cells. In addition, many researchers reported [6][7][8][9][10][11][12] that the soft deposition of TCO films is necessary in preventing damage on the as-deposited ultrathin a-Si:H film [the intrinsic layer is around 5 nm and the doped layer (p or n) is around 10 nm] of SHJ solar cells. It has been reported that the higher quality of TCO films fabricated by reactive plasma deposition (RPD) originates from the lower energy of depositing particles than of sputtering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] In Si solar cells, there have been reports showing that the solar cell performance depends on the deposition conditions of ITO layers. [25][26][27][28] For example, in heterojunction Si with intrinsic thin layer solar cells, 26) ITO electrodes deposited at room temperature (RT), lead to a very low open-circuit voltage V OC due to the passivation degradation of thin-film hydrogenated a-Si layers underneath probably resulting from particle bombardment during the ITO sputtering. Therefore, ITO sputtering is performed at elevated temperatures like 180 °C to recover some of the degradation induced by the ITO sputtering, resulting in an improvement of V OC .…”
Section: Introductionmentioning
confidence: 99%
“…14,17,[19][20][21] Besides the optoelectrical properties of ITO films, sputter damage is another typical problem associated with the deposition process and has been widely reported. 22,23) It is generally believed that during the ion bombardment sputtering of ITO films, the transfer of energy from ions to the substrate generates defects in the crystalline silicon (c-Si) network, which thus deteriorates the c-Si surface passivation provided by a-Si:H. 24,25) Hence, an unsuitable ITO deposition process can severely limit the conversion efficiency of HET solar cells. 26) However, for most of the above-mentioned highefficiency HET solar cells, little information is available on the transparent conductive layer preparation conditions and their effects on the conversion efficiency of the solar cells.…”
Section: Introductionmentioning
confidence: 99%